The Effect of Learning Motivation on Learning Independence Among Eleventh Grade Students at SMA Labschool Universitas PGRI Semarang - Mufidah, Nur Aini; Yuliejantiningsih, Yovitha; Ismah, Ismah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to determine the effect of learning motivation on learning independence among eleventh-grade students at SMA Laboratorium Universitas PGRI Semarang. Learning motivation is considered an important factor in achieving educational goals, while learning independence reflects students' ability to manage their own learning process. This research uses a quantitative approach with a correlational design, involving 87 students who were selected through a questionnaire. The collected data were analyzed using statistical techniques, including descriptive analysis and Pearson correlation. The results show that students' learning motivation and learning independence are in the